PEMANFAATAN KOTORAN SAPI MENJADI BIOGAS DI DESA CILEMBU KABUPATEN SUMEDANG - Sudirman, Maman; Adamy, Zulham; Setiana, Nana; Igiriza, Miftahunnisa; Enceng, Enceng (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Cow dung is still a waste that has not been widely utilized by farmers, even though cow dung can be used as an alternative fuel called biogas. Cilembu is an agribusiness village known for its sweet potato and livestock production. Despite having great potential in livestock, cow dung is often disposed of without being processed first. This Community Service (PkM) was carried out in Cilembu Village, Sumedang Regency. This activity consisted of counseling on the benefits of biogas, the benefits of cow dung, and processing cow dung into biogas. The counseling activity was attended by 25 participants with five livestock families selected as pilot subjects. The participants were given counseling and practical work on biogas production.